Efektivitas Model Cooperative Learning Tipe STAD dan Contextual Teaching and Learning Terhadap Hasil Belajar IPAS Siswa Sekolah Dasar: Systematic Literatur Review - Dea Ayu Angraini; Wesi Salsabela; Walhazwa; Ayatullah Muhammadin Al Fath; Erwin Efendi Hutagalung (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study analyzes and compares the effectiveness of the Student Teams Achievement Divisions (STAD) model with Contextual Teaching and Learning (CTL) in improving elementary school students science learning outcomes. The research gap in this study arises from a lack of teaching innovation due to students low concentration and conceptual understanding of abstract science material, coupled with the need for a comprehensive literature synthesis to determine the advantages of these two models over conventional methods. This research focuses on elementary students cognitive learning outcomes, engagement, and collaboration skills. A Systematic Literature Review (SLR) was employed as the primary research method. Findings indicate that both STAD and CTL significantly. improve student learning outcomes, STAD excels in fostering group accountability through a team progress point system, while CTL strengthens memory retention by connecting content to real-life contexts. This study offers strategic implications for educators to choose STAD to stimulate healthy competitive motivation or CTL to deepen contextual understanding, thereby optimizing the quality of sustainable elementary science education